A Sphinx upon the Dnieper: Black Modernism and the Yiddish Translation of Race. Issue 2 (2021) - Rosenblatt, Eli
Abstract : This article examines the context and content of the 1936 Soviet Yiddish publication of Neger-Dikhtung in Amerike, which remains to this day the most extensive anthology of African-Diasporic poetry in Yiddish translation. The collection included a critical introduction and translations of nearly one hundred individual poems by twenty-nine poets, both men and women, from across the United States and the Caribbean. This article examines the anthology's position amongst different notions of "the folk" in Soviet Yiddish folkloristics and the relationship of these ideas to Yiddish-language discourse about race and racism, the writings of James Weldon Johnson and W.E.B. Du Bois, with whom Magidoff corresponded, and the Yiddish modernist poetry of Shmuel Halkin, who edited the book series in which the anthology appears. When placed alongside Du Bois's and others' visits to the Soviet Union in the 1930s, the appearance of African-American and Caribbean poetry in Yiddish translation shows how a transatlantic Jewish avant-garde interpreted and embedded itself within Soviet-African-American cultural exchange in the interwar years. Magidoff served as a Soviet correspondent for NBC and the Associated Press from 1935. He was accused of espionage and expelled from the USSR in 1948.